Genome-wide association study of feruloyl arabinoxylan content in common wheat grain. (September 2019) - Zhan, Shuaishuai; Ren, Yi; Liu, Jindong; Fuerst, E. Patrick; Xia, Xianchun; Lv, Wenjuan; Morris, Craig F.; Geng, Hongwei
Abstract: Arabinoxylan (AX) is an important component of dietary fiber, and exerts significant effects on the processing quality and nutritional value of flour. Feruloyl arabinoxylan (FAX) is a major factor influencing the functional properties of AX. Here, a genome-wide association study (GWAS) was conducted for FAX content using a high-density SNP platform. FAX content was evaluated in 256 wheat varieties (two populations) in four environments. Results showed that 83 and 33 marker-trait associations (MTAs) for FAX content were identified, explaining 6.7–9.2% and 10.2–21.2% phenotypic variation in the two populations. Two and three MTAs were repeatedly detected in at least two environments. Five MTAs were detected in both populations. Linear regression indicated a clear dependence of FAX content on the number of favorable alleles, indicating that QTL pyramiding would be an effective approach to modify FAX content. Associated with these significant MTAs, five candidate genes: isoflavone reductase, carnitine dehydrogenase, acylamino acid releasing enzyme, glucose isomerase, and GMP synthase were found to be involved in FAX biosynthesis. Lastly, our study contributes important information for genetic improvement of wheat quality and contributes to developing marker-assisted selection. Highlights: 83 and 33 marker-trait associations (MTAs) for FAX content were identified by GWAS. 5 MTAs were detected in both populations. 5 varieties in each of 2 populations had more favorable alleles and higher FAX content. 5 candidate genes were found to be involved in FAX biosynthesis.